Human resources management and evaluation system based on fuzzy analytic hierarchy process - Yu, Shasha (Journal of interdisciplinary mathematics, 2017)
The basic principle of evaluation system design has been discussed; internal logic relation between the specific content of evaluation and its evaluation system has been analyzed from seven factors, including enterprise internal and external environment and evaluation subject, evaluation object, evaluation target, evaluation principle, evaluation system, evaluation implementation and evaluation report; the significance of evaluation index on evaluation system has been pointed out emphatically. Deep research on the key parts of evaluation index, evaluation standard and evaluation method in evaluation system has been made. In the end, explain how to evaluate human resources management with analytic hierarchy process and fuzzy comprehensive evaluation method by studying the examples of F Group and point out the problems may possibly appear in the application of evaluation model and the solutions.